PENGARUH INTELLECTUAL CAPITAL, KARAKTERISTIK PERUSAHAAN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Fauzia, Norma; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of intellectual capital, ownership structure, growthopportunity and CSR disclosure to the firm value. The population of this research is manufacturing sectorcompanies which are listed in Indonesia Stock Exchange (IDX) which have been taken by using purposivesampling. The data uses financial data from the years of 2012 to 2014. The result of this research shows that: (1)Intellectual capital has positive influence to the firm value because when the intellectual capital which has beenallocated, it can increase the firm value; (2) Managerial ownership does not have any influence to the firm value,it is caused by a low proportion of the managerial ownership owned by the management (3) Institutionalownership does not have any influence to the firm value because there is asymmetric information between themanagement and the institutional investors (4) Growth Opportunity does not have any influence to the firmvalue because of the uncertain factor in the future. (5) CSR disclosure has positive influence to the firm value,because when the company has done a lot of CSR disclosure it will make company image good and impact to theenhancement of firm value.Keywords: intellectual capital (VAIC), ownership structure (MANJ & INST), growth opportunity(GROWTH), CSR disclosure (CSDI), firm value (PBV).